The Effect of Interests, Personality and Compliance with Organizational Regulations on the Responsible Character at MB UMS - Prasetya, Rayhan Firman; Prasetiyo, Wibowo Heru (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This Research aims to determine the effect of interest on the responsible character of Marching Band UMS members, to determine the effect of students' personality traits on the responsibility of Marching Band UMS members, to determine the effect of organizational regulations on the responsibility of Marching Band UMS members, and to determine the join effect of interest, personality, and compliance with organizational regulations on the responsible Character at Marching Band UMS members. Methodology: This research uses quantitative research methods. The sample in this study was 105 people consisting of administrators and members of the UMS marching band. Results: The results of this research show that there is a significant influence between student interests, personality and compliance with organizational regulations on responsible character. UMS marching band members have implemented the character of responsibility well in daily training and in maintaining the equipment they use. Applications/Originality/Value: This research provides a contribution to future researchers and can be used as additional information regarding the character of a person's responsibility.